Dynamics of premixed methane/air mixtures in a heated microchannel with different wall temperature gradients. Issue 4 (12th January 2017) - Kishore, V. Ratna; Minaev, S.; Akram, M.; Kumar, Sudarshan
Abstract : The unsteady flame propagation mode (FREI) is affected by the wall temperature gradient. As the temperature gradient approaches zero, the mixture ignites at its auto-ignition temperature, frequency decreases and this leads to extinction of FREI mode. Abstract : The observation of various flame propagation modes for externally heated tubes has led to many fundamental studies aimed at understanding flame propagation in microtubes. During these studies, it has been observed that for moderately low flow velocities, flames with repetitive extinction and ignition (FREI) have been observed to exist in various experimental, theoretical and numerical studies. The formation of these FREI flame modes depends on various parameters such as channel dimensions, wall temperature gradient, flow rates and mixture type. In the present work, an effort has been made to understand the effect of the wall temperature gradient on the FREI phenomenon through a 1 mm diameter circular tube using 2D numerical studies with detailed GRI Mech3.0 for premixed methane/air mixtures. The different wall temperature gradients analyzed are varied from 33.3–1 K mm −1, with an upper range corresponding to experimental conditions. Five different phases of flame propagation have been observed during the FREI flame propagation mode. The entire fuel gets consumed during the cycle and a significant amount of unburned CO remains during the weak reaction phase, towards the extinction of FREI mode. The effect of the wall temperature gradient on the FREI ignition phenomenon has been investigated to understand the development of ignition kernels. It is observed that the ignition happens at the axis and not at the wall of the channel. This happens due to a boundary-layer phenomenon discouraging ignition at the wall. It has been observed that a decrease in the temperature gradient results in movement of the ignition point towards the low-temperature region. The peak CO value increases with a decrease in the wall temperature gradient.